Vocabulary Learning and Retention in Light of Textual and Aural Input Enhancement - Farrokh, Parisa; Hasani, Yaser (LANGUAGE ART, 2025)
The present study focused on the effect of textual input and aural input enhancement on Iranian intermediate English learners’ vocabulary learning and retention. This study adopted a quasi-experimental design. 60 intermediate English learners from high school were selected as the participants. To ascertain the homogeneity of the students, a placement test was administrated to establish the participants’ homogeneity prior to the study. Next they were randomly divided into two experimental groups and one control group. A pretest of vocabulary was administered to all groups. After that the experimental groups received textual enhancement and aural input. While, the control group received no treatment. After sixteen sessions, immediate posttest of vocabulary, similar to pretest was administered to all participants. Delayed posttest of vocabulary was given two weeks later. The results of ANOVA analysis and paired sample t-tests revealed that using textual input enhancement and aural input led to better performance of the participants in the vocabulary learning and retention (p<0.05). However, the extent of improvement that occurred was not the same for the two experimental groups; that is, textual enhancement input would help learners, more in learning and retention of vocabulary than aural input.